Breaking The Silence: Speaking Anxiety among Tenth Graders at SMAN 1 Luwu Utara - Basitha, Tiara Annur; Marhum, Mochtar; Maf’ulah (English Language Teaching Methodology, 2025)
Speaking anxiety is a common barrier that students face in language learning, particularly in situations requiring verbal communication. This study investigates the factors, causes, and strategies to overcome speaking anxiety among tenth-grade students at SMA Negeri 1 Luwu Utara. Employing a descriptive qualitative design, data were collected through interviews and questionnaires. Findings revealed three primary forms of speaking anxiety: communication anxiety, test anxiety, and fear of negative evaluation. Key causes included limited vocabulary, fear of mistakes, and low self-confidence. To address these issues, students adopted strategies such as preparation, positive thinking, and relaxation techniques. This research highlights the urgency of fostering a supportive classroom environment that reduces anxiety and promotes active participation, offering valuable insights for educators seeking to enhance student engagement and communication skills. By identifying both the root causes and coping strategies, the study contributes to a deeper understanding of how to effectively support students facing speaking anxiety.